The establishment and verification of kinematic equation of all link centroid of the manipulator mounted on a satellite. (April 2019) - Zhang, Hongwen; Zhu, Zhanxia; Tang, Biwei; Yuan, Jianping
When using space robot to capture target like failed satellite, the force impulse between the target and the end-effector of space robot will load the base satellite with additional momentum abruptly. When capture happens, the pre-impact configuration can influence augmentations of partial momentum of the base and the manipulator. In order to realize a pre-impact configuration, which can reduce the partial momentum augmentations, the control of all link centroid together with end-effector by path planning is very important. In this paper, we establish a basic velocity kinematic equation for all link centroid, which describes the basic linear kinematic relationship between the linear velocity of all link centroid and linear and angular velocities of the base, joint angular velocity of the manipulator, where this basic velocity kinematic equation can be developed into kinematic equations for all link centroid under different kinds of working modes such as free-floating working mode. All link centroid can be controlled by path planning with this equation. Besides, velocity kinematic equation for all link centroid of space robot under a specific working mode is similar to the velocity kinematic equation for end-effector of space robot under the same working mode, so all link centroid can be controlled together with end-effector by path planning. We have derived velocity kinematic equations for all link centroid of space robot with a free-floating base and a fixed base. Both of them are verified by numerical simulations. The motions of position and attitude of the base and the manipulator end caused by all link centroid motion are also shown by simulation study. We also realize the simultaneous path tracking of all link centroid and end-effector for a fixed base space robot.